2017
DOI: 10.1007/978-1-4939-6869-5_15
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage T4 as a Nanoparticle Platform to Display and Deliver Pathogen Antigens: Construction of an Effective Anthrax Vaccine

Abstract: Protein-based subunit vaccines represent a safer alternative to the whole pathogen in vaccine development. However, limitations of physiological instability and low immunogenicity of such vaccines demand an efficient delivery system to stimulate robust immune responses. The bacteriophage T4 capsid-based antigen delivery system can robustly elicit both humoral and cellular immune responses without any adjuvant. Therefore, it offers a strong promise as a novel antigen delivery system. Currently Bacillus anthraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…WT T4 was propagated on E. coli P301 as described previously. 46 T4(C) is a mutant containing an amber mutation at amino acid 58 of gene 42 that codes for dCMP hydroxymethylase and an amber mutation at amino acid 124 of gene 56. 30 To prevent accumulation of spontaneous revertants, the T4(C) mutant was propagated on E. coli B834 for only one generation.…”
Section: Methodsmentioning
confidence: 99%
“…WT T4 was propagated on E. coli P301 as described previously. 46 T4(C) is a mutant containing an amber mutation at amino acid 58 of gene 42 that codes for dCMP hydroxymethylase and an amber mutation at amino acid 124 of gene 56. 30 To prevent accumulation of spontaneous revertants, the T4(C) mutant was propagated on E. coli B834 for only one generation.…”
Section: Methodsmentioning
confidence: 99%
“… E. coli strains DH5α was used for cloning. E. coli strain P301 was used to propagate hoc − soc − phage T4 as described previously ( 49 51 ). The E. coli BL21-CodonPlus (DE3)-RIPL cells (Agilent Technologies, Santa Clara, CA) were used for expression of genes encoding target proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Hoc − Soc − T4 phages were purified as described previously ( 48 , 49 ). Briefly, the propagated T4 phage on E. coli P301 was collected by centrifugation for 45 min at 25,000 × g .…”
Section: Methodsmentioning
confidence: 99%
“…Most phages have more than one structural protein that can be used to display and, therefore, are able to link the antigen and the DC-targeting molecule to the same VLP. For example, we have shown that the two nonessential capsid proteins, Hoc and Soc, of phage T4 can be used to simultaneously display two different foreign proteins (Li et al., 2007; Shivachandra et al., 2007; Tao et al., 2017a), one an antigen and another a DC-targeting molecule (e.g., a monoclonal antibody against DEC-205) (Tao et al., 2013b).…”
Section: Applications Of Phages In Infectious Diseasementioning
confidence: 99%